Türk Dili ve Edebiyatı Alanında Yapılan Doktora ve Yüksek Lisans Tezleri Bibliyografyası (1987-1999) I - Kazan, Şevkiye (Kitabevi, 2002)
In this article a thesis bibliography has been formed on Turkis Language and literature through collecting several articles defining thesis works and information sources of the institutions gathering necessary knowledge on this subject. The work has been divided in four parts. Folk Literature, New Turkish Literature, Turkish Language and Old Turkish Literature. In this article fırst two topics which are Folk and New Turkish Literature have been published. The rest will be published in coming issues.
A Bibliyographic Study on the Ph. D. and M.A Theses Done Between 1987-1999 on Turkish Language and Literature I
Keywords: Bibliography; Turkish Language and Literature; Turkish Folk Literature; Bibliography on Turkology; Theses